Unwriting Maya literature : ts'íib as recorded knowledge - Worley, Paul M., 1976-; Palacios, Rita M. (The University of Arizona Press, 2019)
"This volume provides a decolonial framework for reading Maya and Indigenous texts"--Provided by publisher